2013
DOI: 10.1007/s11262-013-0877-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel subtype of feline immunodeficiency virus in a population of naturally infected felines in the Brazilian Federal District

Abstract: The feline immunodeficiency virus (FIV) is a retrovirus that is found worldwide, and it can be assigned to six subtypes (A, B, C, D, E, and a putative subtype F) based on sequencing analysis of the env and gag genes. Subtypes A and B are the most common worldwide. In Brazil, several authors have isolated only subtype B, and its prevalence differs markedly among investigated populations. Blood samples from 200 domestic felines from the Federal District in Brazil were analyzed by PCR. Samples that tested positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The present study showed a higher positivity percentage for the PCR technique when compared to Marçola et al (2013), that related 2% (4/200) of positive animals in Distrito Federal (GO) and to the studies done by Caxito et al (2006), Teixeira et al (2007) and Alves et al (2011), in the city of Belo Horizonte (MG) presenting values of 2.7% (12/450), 4.14% (6/145) and 6.41% (5/78), of positivity, respectively. However, the values found in São Luís (MA) were lower than the ones related by Lara et al (2008) that reported an occurrence of 14.8% (67/454) of felines from 13 cities of São Paulo state and by Souza et al (2002) who verified positivity of 20.2% in Rio de Janeiro (RJ) and even lower than those found by Caldas et al (2000) who described 37.5% (15/40) of seropositive animals in the state of Rio Grande do Sul.…”
Section: Discussioncontrasting
confidence: 41%
“…The present study showed a higher positivity percentage for the PCR technique when compared to Marçola et al (2013), that related 2% (4/200) of positive animals in Distrito Federal (GO) and to the studies done by Caxito et al (2006), Teixeira et al (2007) and Alves et al (2011), in the city of Belo Horizonte (MG) presenting values of 2.7% (12/450), 4.14% (6/145) and 6.41% (5/78), of positivity, respectively. However, the values found in São Luís (MA) were lower than the ones related by Lara et al (2008) that reported an occurrence of 14.8% (67/454) of felines from 13 cities of São Paulo state and by Souza et al (2002) who verified positivity of 20.2% in Rio de Janeiro (RJ) and even lower than those found by Caldas et al (2000) who described 37.5% (15/40) of seropositive animals in the state of Rio Grande do Sul.…”
Section: Discussioncontrasting
confidence: 41%
“…Only one cat had FIV infection, which was expected considering the low frequency of such retrovirus in the region studied (Marcola et al 2013). This cat had a co-infection of Candidatus Mycoplasma haemominutum and FeLV with typical clinical signs from FeLV such as low PCV, erythrocytes and hemoglobin, that could have been caused by the associated infection between Candidatus Mycoplasma haemominutum and FeLV, and changes associated with FIV like PPT above reference values and low number of platelets (data not show).…”
Section: Resultsmentioning
confidence: 72%
“…Importantly, however, viral phylogenies based on a single gene (as here) have been previously used to establish viable classification schemes. Notable examples include members of genus Enterovirus (Mirand et al, 2006;Oberste et al, 1999), pestiviruses such as BVDV-1 (Deng et al, 2012;Vilcek et al, 2001) and BVDV-2 (Flores et al, 2002;Jenckel et al, 2014;Weber et al, 2015), circoviruses such as PCV2 (Franzo et al, 2015;Grau-Roma et al, 2008;Segalés et al, 2008), and lentiviruses such as FIV (Marçola et al, 2013;Sodora et al, 1994). In the case of IBV we propose that an effective classification scheme, particularly the designation of lineages and genotypes, should be based on clearly identifiable genetic groups (i.e.…”
Section: Discussionmentioning
confidence: 99%